Perlindungan Hukum Tenaga Kerja Kontrak dalam Perjanjian Kerja Waktu Tertentu Berdasarkan Undang-Undang Nomor 6 Tahun 2023 Tentang Cipta Kerja - Muhammad Rijal Sabilulhaq (Faculty of Social, Politic, and Law Science, Universitas Serang Raya, 2025)
This article examines the legal protection for contract workers employed under Fixed-Term Employment Agreements (PKWT) following the enactment of Indonesian Law Number 6 of 2023 concerning the Stipulation of Government Regulation in Lieu of Law Number 2 of 2022 on Job Creation into law (Job Creation Law 2023). The research aims to identify the forms of legal protection provided to contract workers and to analyze the substantive changes regarding PKWT provisions under the 2023 Job Creation Law. The research employs a normative legal approach with library study methods, examining relevant statutory provisions and academic literature. The study finds that Law No. 6 of 2023 introduces new protections for contract workers, including regulations on compensation rights, social security entitlements, and flexibility in contract renewals. However, the increased flexibility afforded to employers may also pose legal uncertainty and challenges for safeguarding worker rights.